The importance of auxiliary materials and techniques of watercolor painting in the performance of creative tasks by students in academic and independent activities - Scherbakova, L.A. (Pedagogy of Higher and Secondary Education, 2006)
Value of auxiliary materials and mechanic: water colour painting al performaner by studets of creative tasks on the academic aid independent occupations. In the article arc examined the problem of perfecting the instruction of students, who learned on first counts of the artisncally-graphic faculties, to the water-color painting at the special course "Technology of the water-color painting".